A proposal for the reconstruction of a historical masonry building constructed in Ottoman Era (Istanbul). (November 2020) - Akcay, Cemil; Şolt, Ayşen; Korkmaz, Nail Mahir; Sayin, Baris
Abstract: The present study includes a reconstruction proposal based on the original architectural and structural features of a historical masonry barrack building, which was built as a military barracks in 1866 and then demolished in the last 1940s. The building under the investigation is one of the first structures, in the historical peninsula, constructed by using industrial bricks in the Ottoman period. The study comprises of two stages, namely, the determination of the original architectural and structural features, as well as the historical process research focused on the building. The process from the date that the building was built to the time in which it was demolished was surveyed through historical documents and old photographs. In the second stage, georadar and electromagnetic field measurements were performed to determine whether archaeological remains exist in the area where the building is located. Evaluating the data obtained from the first two stages, floor plans, facade views, construction type, and material properties of the building were determined. The presented procedure in the study can be used as a reconstruction approach of the partly or completely demolished historical masonry buildings. Highlights: The study presents a methodological approach to the reconstruction process of a demolished masonry building. The historical process of the demolished building is investigated based on historical documents and old photographs. Georadar and electromagnetic wave measurements are performed in the location of the demolishedbuilding. Floor plans, facade views, construction type, and material properties of the building were determined.